2021
DOI: 10.1111/pace.14249
|View full text |Cite
|
Sign up to set email alerts
|

Impact of His bundle pacing on right ventricular performance in patients undergoing permanent pacemaker implantation

Abstract: Background His‐Bundle pacing (HBP) is an emerging technique for physiological pacing. However, its effects on right ventricle (RV) performance are still unknown. Methods We enrolled consecutive patients with an indication for pacemaker (PM) implantation to compare HBP versus RV pacing (RVP) effects on RV performance. Patients were evaluated before implantation and after 6 months by a transthoracic echocardiogram. Results A total of 84 patients (age 75.1±7.9 years, 64% male) were enrolled, 42 patients (50%) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…His‐Bundle pacing permits ventricular stimulation without crossing the tricuspid valve in some patients. Thanks to the more physiologic ventricular activation, His‐bundle and left bundle branch pacing may reduce the functional component and decrease TR 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…His‐Bundle pacing permits ventricular stimulation without crossing the tricuspid valve in some patients. Thanks to the more physiologic ventricular activation, His‐bundle and left bundle branch pacing may reduce the functional component and decrease TR 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…We systematically assessed studies on HBP with an assessment of TR, which comprised of 9 original research articles and 1 case series reporting nearly 5 years of experience from 546 patients across centers around the world (Grieco et al, 2021 ; Hasumi et al, 2018 ; Hu et al, 2020 ; Hu et al, 2021 ; Huang et al, 2019 ; Ma et al, 2021 ; Shan et al, 2018 ; Vijayaraman et al, 2017 ; Wu et al, 2021 ; Ye et al, 2021 ). This is the first systematic analysis of a patient cohort to demonstrate the incidence of TR with HBP and its quantification before and after the procedural follow‐up, demonstrating its effects on ventricular synchrony.…”
Section: Discussionmentioning
confidence: 99%
“…HBP can also normalize conduction in patients with bundle branch block (BBB), hence, it has a role as an alternative to CRT (Abdelrahman et al, 2018 ). As HBP lead can be implanted above tricuspid annulus, its effect on TV morphology is minimal, leading to reversal of TR (Grieco et al, 2021 ; Hasumi et al, 2018 ; Hu et al, 2020 ; Hu et al, 2021 ; Huang et al, 2019 ; Ma et al, 2021 ; Shan et al, 2018 ; Vijayaraman et al, 2017 ; Wu et al, 2021 ; Ye et al, 2021 ). In this systematic review, we provide an association of TR in patients undergoing HBP.…”
Section: Introductionmentioning
confidence: 99%
“…These all suggested that ventricular electrical and mechanical dyssynchrony may be the key cause for TR, whether the electrodes cross the valve or not. Recently, Grieco et al (30) FIGURE 2 Comparison of tricuspid regurgitation velocity and cardiothoracic ratio before and after implantation of HPSP for 3 months. (A) Tricuspid regurgitation velocity significantly decreased after implantation of HPSP for 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…These all suggested that ventricular electrical and mechanical dyssynchrony may be the key cause for TR, whether the electrodes cross the valve or not. Recently, Grieco et al ( 30 ) explored the influence of HBP and RVP on right heart function and found that compared with RVP, although some HBP electrodes crossed the tricuspid valve and were located under the valve, parameters of right heart function such as tricuspid regurgitation, PASP, TAPSE and RV-FAC were significantly improved at 6 months. A study using 3D echocardiography showed moderate-to-severe tricuspid regurgitation reduced to mild in patients after HBP, even though the electrodes crossed the tricuspid valve ( 31 ).…”
Section: Discussionmentioning
confidence: 99%